HUBUNGAN TINGKAT PENGETAHUAN MENYIKAT GIGI DENGAN INDEKS GINGIVA SISWA MADRASAH TSANAWIYAH. Tinjauan Terhadap Siswa MTs di Kabupaten Barito Kuala - Dana Chitra Maida; Widodo Widodo; Rosihan Adhani (Dentin, 2017)
ABSTRACTBackground: Low of knowledge about health can be a predisposing factor for the onset of a disease. The knowledge about health is very important, because knowledge as a cognitive domain will influence health attitudes and behavior of a person, especially preventive and healing of a disease as well as effect on health status. Epidemiological studies said that the oral hygiene and gingival health status of each severe are generally found in children and adolescents. Purpose: This study aims to find out the correlation of teeth brushing knowledge level with gingival index on Madrasah Tsanawiyah students in Barito Kuala. Methods: This research method is quantitative analytic using Cross Sectional approach at 100 students of Madrasah Tsanawiyah in Barito Kuala. Questionnaire instrument was used to measure students’ knowledge level of teeth brushing and gingival index to students’ gingival conditions. Results: The results is teeth brushing knowledge Madrasah Tsanawiyah students in Barito Kuala have a good category with ≥75% of knowledge score. Gingival index Madrasah Tsanawiyah Students in Barito Kuala on a score of 0.1-1.0 or have a gingival status sustained a mild inflammation. Conclusion: There is a meaningful connection between the knowledge of brushing teeth with gingival index of Madrasah Tsanawiyah students in Barito Kuala p=0.001 or (p<0.05). Keywords: Teeth brushing knowledge level, gingival index, behavior  ABSTRAKLatar Belakang: Rendahnya pengetahuan seseorang mengenai kesehatan dapat menjadi faktor predisposisi timbulnya suatu penyakit. Pengetahuan mengenai kesehatan merupakan hal yang sangat penting, karena pengetahuan sebagai domain kognitif akan mempengaruhi sikap dan perilaku kesehatan seseorang khususnya tindakan pencegahan dan penyembuhan terhadap penyakit serta berpengaruh terhadap status kesehatan. Studi epidemiologi menyebutkan bahwa kebersihan rongga mulut dan status kesehatan gingiva dari tiap tingkat keparahan pada umumnya didapatkan pada anak-anak dan remaja. Tujuan: Mengetahui hubungan tingkat pengetahuan menyikat gigi dengan indeks gingiva siswa Madrasah Tsanawiyah di Kabupaten Barito Kuala. Metode: Penelitian yaitu kuantitatif analitik dengan pendekatan Cross Sectional pada 100 siswa Madrasah Tsanawiyah di Kabupaten Barito Kuala. Instrumen kuisioner digunakan untuk mengukur tingkat pengetahuan menyikat gigi siswa dan indeks gingiva untuk mengukur kondisi gingiva siswa. Hasil: Penelitian didapatkan pengetahuan menyikat gigi siswa Madrasah Tsanawiyah di Kabupaten Barito Kuala berada pada kategori baik dengan skor pengetahuan ≥75%. Indeks gingiva siswa Madrasah Tsanawiyah di Kabupaten Barito Kuala berada pada skor 0,1-1,0 atau status gingiva mengalami peradangan ringan. Kesimpulan: Terdapat hubungan yang bermakna antara tingkat pengetahuan menyikat gigi dengan indeks gingiva siswa Madrasah Tsanawiyah di Kabupaten Barito Kuala p=0,001 atau (p<0,05).  Kata Kunci: Tingkat pengetahuan menyikat gigi, indeks gingiva, perilaku